Cursed horses - Németh, György; Gradvohl, Edina (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
A small lead tablet with the drawing of a horse’s head is kept in the collection of the Musée Bargoin in Clermont-Ferrand. This study examines depictions of horses on curse tablets and magic gems and concludes that no examples of such depictions have been found so far.